Integrated Mapping of Yaws and Trachoma in the Five Northern-Most Provinces of Vanuatu. - Fasihah Taleo; Colin K Macleod; Michael Marks; Oliver Sokana; Anna Last; Rebecca Willis; Mackline Garae; Annie Bong; Brian K Chu; Paul Courtright; Jacob Kool; George Taleo; et al. (Public Library of Science (PLoS), 2017)
Yaws and trachoma are targeted for eradication and elimination as public health problems. In trachoma-endemic populations mass administration of azithromycin can simultaneously treat yaws. We conducted a population-based prevalence survey in the five northernmost provinces of Vanuatu, where trachoma and yaws are suspected to be co-endemic. Clinical signs of trachoma were evaluated using the WHO simplified grading system, and skin examination with a serological rapid diagnostic test used to identify yaws. We enrolled 1004 households in 59 villages over 16 islands, and examined 3650 individuals of all ages for trachoma. The overall adjusted prevalence of trachomatous inflammation-follicular (TF) in 1-9 year-olds was 12.0% (95% Confidence Interval: 8.1-16.7%), and the overall adjusted prevalence of TT in those aged 15 years and greater was 0.04% (95% CI 0-0.14%). In multivariate analysis, the odds of children having TF was 2.6 (95% CI = 1.5-4.4) times higher in households with unimproved latrines, and independently associated with the number of children in the household (OR 1.3, 95% CI = 1.0-1.6 for each additional child). We examined the skin of 821 children aged 5-14 years. Two children had yaws, giving an estimated prevalence of active yaws in those aged 5-14 years of 0.2% (95% CI = 0.03-0.9%). Mass treatment with azithromycin is recommended in these provinces. Given the apparent low burden of yaws, integration of yaws and trachoma control programmes is likely to be useful and cost-effective to national programmes.